Effect of mussel-inspired polydopamine on the reinforced properties of 3D printed β-tricalcium phosphate/polycaprolactone scaffolds for bone regeneration. Issue 1 (14th November 2022) - Ho, Chia-Che; Chen, Yi-Wen; Wang, Kan; Lin, Yen-Hong; Chen, Ta-Cheng; Shie, Ming-You
Abstract : 3D printed mussel-inspired polydopamine-coated β-TCP/polycaprolactone scaffolds have been considered potential grafts that facilitated not only the physicochemical behaviors but also stimulated the formation of neo-bone tissue in femur defects. Abstract : Bioceramic/polymer scaffolds have been considered as potential grafts used for facilitating bone healing. Unfortunately, the poor interfacial interaction between polymer matrices and bioceramic fillers limited their use in practical medicine. Thus, a facile strategy for reinforcing the three-dimensional printed β-tricalcium phosphate/polycaprolactone scaffolds through employing polydopamine modified-ceramics as fillers. The effects of the dopamine precursor on the compressive strength, degradability, cell proliferation, osteogenic differentiation, and in vivo osteogenicity were measured. The results indicated that the concentration of dopamine could remarkably affect the thickness and density of the polydopamine layer on fillers, further varying the compressive strength (1.23-fold to 1.64-fold), degradability, and osteogenicity of the scaffolds. More importantly, the presence of polydopamine in the three-dimensional printed composite scaffolds not only facilitated the proliferation, alkaline phosphatase activity and mineralization of mesenchymal stem cells, but also stimulated the formation of neo-bone tissue in femur defects. Taking together, the proposed scaffolds might serve as a candidate for bone regeneration.